2009
DOI: 10.1080/01638530902959448
|View full text |Cite
|
Sign up to set email alerts
|

Narrative and Paradigmatic Explanations in Preschool Science Discourse

Abstract: This study examines the use of narrative and paradigmatic modes of explanation in large group discussions about science in preschool classrooms. Participants comprised students and teachers in 29 preschool classrooms, 19 of which used the ScienceStart! curriculum, a hands-on, inquiry approach to teaching science with young children. Analyses of videotaped large group activities address two major research questions: (a) Does the use of a structured preschool science curriculum promote the use of paradigmatic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
0
16
0
7
Order By: Relevance
“…Results indicated significant impacts on four of eight school readiness domains, including math, with a trend signifying potential impacts on science. In another study of an early childhood science curriculum, Peterson (2009) provided ScienceStart! and associated professional development to 19 educators, with additional educators serving in a comparison condition.…”
Section: Improving Early Math and Science Education Through Professiomentioning
confidence: 99%
“…Results indicated significant impacts on four of eight school readiness domains, including math, with a trend signifying potential impacts on science. In another study of an early childhood science curriculum, Peterson (2009) provided ScienceStart! and associated professional development to 19 educators, with additional educators serving in a comparison condition.…”
Section: Improving Early Math and Science Education Through Professiomentioning
confidence: 99%
“…A review of the literature showed that intervention programs which emphasize various features to support the development of maths skills (Aunio, Hautamaki & Van Luit, 2005;Kinzie et al, 2014;Klein, Starkey, Clements, Sarama & Lyer, 2008;Missal, Hojnoski, Caskie & Repasky, 2015;Presser, Clements, Ginsburg & Ertle, 2015) and science skills (Gelman & Brenneman, 2004;Hong & Diamond, 2012;Mantzicopoulos, Samarapungavan & Patrick, 2009;Nilsson, 2015;Peterson, 2009;Peterson & French, 2008) in children and which include teacher supported education and family participation have a positive impact. Although we did not find any studies in the literature that examine the development of maths and science skills in pre-school children through the use of mind maps, it is nonetheless known that preparing mind maps gives children the opportunity to implement many skills, such as counting, establishing cause-effect relationships, rhythm, classifying, detailing, using colours and shapes, and spatial awareness (Buzan & Buzan, 2015;Buzan, Dottino & Israel, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Included among these programs are "Let's Count" , "Let's Think", "Big Maths for Little Kids" , "The Number Worlds" , "Building Blocks", "The Pre-K Maths Curriculum", "Storytelling Sagas" , "High Scope-Number Plus (Maths education program for young children)" (Aunio, Hautamaki & Van Luit, 2005;Ginsburg, Lee & Boyd, 2008;Perry & MacDonald, 2015;Presser, Clements, Ginsburg & Ertle, 2015) "Science Start!" , "Scientific Literacy Project" , "Wings of Discovery", and "Tool Kit for Early Childhood Science Education" (Alabay, 2011;Mantzicopoulos, Patrick & Samarapungavan, 2008;Peterson, 2009), all of which aim to develop science skills. Examples of the programs that support the development of both science and maths skills are "Preschool Pathways to Science" and "My Teaching Partner" (Gelman & Brenneman, 2004;Kinzie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The program places a strong importance on using content that is relatable to children's everyday lives, cohesion, and integration across all domains of preschool learning. The effectiveness of the language development portion of the program has been empirically supported by studies of children's discourse (such as asking questions), use of explanations, and scores on the Peabody Picture Vocabulary test (French, 2004 ;NRC, 2005 ;Peterson, 2009 ;Peterson, & French, 2008 ). Student outcome measures on other aspects of scientifi c thinking and learning, however, have not yet been assessed.…”
Section: Learning To Do Sciencementioning
confidence: 98%